Extracellular and intracellular signaling - Adams, James D., Jr. (James David); Parker, Keith K. (Keith Krom); Royal Society of Chemistry (Great Britain) (Cambridge, UK : RSC Publishing, 2011)
A'Intracellular cell signaling is a well understood process. However, extracellular signals such as hormones, adipokines, cytokines and neurotransmitters are vital to the process and have been largely ignored in other works on signaling. They are causative agents in hypertension, diabetes, heart disease, arthritis and other diseases. Aimed at medical professionals and pharmaceutical specialists, this book integrates for the first time extracellular and intracellular signaling processes and offers a fresh perspective on new targets for drug development. With contributions from leading international authorities, it is the result of close cooperation between the authors of the various chapters. Readers are introduced to a new approach to disease causation by adipokines and toxic lipids. Heart disease, migraines, stroke, Alzheimer's disease, diabetes, cancer, and arthritis are approached from the perspective of toxic lifestyle and accumulation of toxic proteins and lipids. Evidence is presented that by alterations in toxic lifestyles you can reduce the incidence of such diseases. New therapeutic targets involving adipokines, ceramide and endocannabinoids are also discussed.'--Back cover.
Includes bibliographical references and index.
Keywords: Cellular signal transduction; Cell interaction; Drug development